Improving Food & Beverage Industry Performance With Performance Prism And AHP (Analytical Hierarchy Process) Method In The Era Of Digital Transformation - Andika, Arby; Octavia, Chendrasari Sari; Dewi, Fitriya Gemala; Subaderi, Subaderi; Hariyanto, Krisnadi (Journal of System Engineering and Technological Innovation, 2024)
MSMEs in the food and beverage industry are one of the leading sectors in Surabaya. MSMEs in the food and beverage industry still experience many difficulties in their development, especially in marketing, there is also the use of technology, lack of innovation, and low quality of human resources. Other obstacles often faced by MSMEs that are members of consumer cooperatives are marketing, many competitors and maintaining existing markets. In addition, MSME owners also pay less attention to marketing strategies and maintaining customer relationships. The quality of service in this case is closely related to sales which have a reference to the performance of the MSME. Problem identification in this study is the unknown improvements to improve the performance of MSMEs, the unknown most effective way to improve stakeholder satisfaction and the unknown strategies that must be carried out, the processes needed to achieve these goals, and the capabilities that must be prepared to implement them in order to achieve the target. Measuring the performance of food and beverage MSMEs by identifying KPIs (Key Performance Indicators) and the performance prism method consists of five perspectives, satisfaction, contribution, strategy, process, and capability. The results of the study were obtained based on the processing of key performance indicators (Key Performance Indicators, KPI) with the highest weighting value from each stakeholder . The KPI with the highest weighting will be applied to the proposed improvements. By making improvements to these indicators, it is expected to improve the performance of MSMEs in the future.